Perlindungan terhadap Harta (Perspektif al-Maqashid al-Syariah) - Asmuni Mth. (Millah: Journal of Religious Studies, 2006)
One of Islamic law purposes is to protect of wealth, either positive protection or negative protection. The positive preserving can be implemented by giving punishment to whom steal the other wealth, or by giving compensation to whom broke the other wealth. The negative preserving can be implemented by investing in order to improve the wealth, and to circulate the riches and also to creating social justice in the society. There is some rules and standardization in the infestation that must be considered. The rules and the standardization those of faith and moral, social and economic development, “la dhara wa la dhirara"' and balances honor and sharing of profit and lost proportionally.